Uses and gratifications of the internet among university of Lagos undergraduates (Journal for Studies in Humanities and Social Sciences, 2019)
This study sought to ascertain how UNILAG students use the internet and the motivation behind the usage pattern. The study was guided by four research questions that sought to establish the level of internet usage among the students; major activities carried out on the internet; the gratifications derived from the online activities and; whether or not their internet activities have any link with the gratification they hoped to derive from such activities. The study is anchored on the uses and gratifications theory which perceives audiences to be active, rather than passive users of media and their messages. The survey research design was used, and data was collected using a questionnaire targeted at 220 respondents selected using the multi-stage sampling technique. The study’s findings were analysed using SPSS and presented in basic frequency tables and percentages. Findings from the study showed that all UNILAG undergraduates use the Internet with 75. 4 per cent of them using it on daily basis with the major access point being the mobile phone. The most practised internet activity was social networking with a 35. 5 per cent response. A majority (93.1%) said their online activities are informed by the gratifications they hope to derive, while 6.9 per cent disagreed affirming the relevance of the uses and gratifications theory. This study recommends that UNILAG students should maximize the opportunities provided by the internet for academic purposes.